(untitled) (Research, Society and Development, 2022)
Maytenus ilicifolia is a plant native to South America, where its leaves are widely used for various treatments thanks to its antiulcerogenic, antimicrobial, anthelmintic, anticancer, hypoglycemic, anti-inflammatory, hypotensive, healing, antioxidant, among others. Therefore, having a wide range of actions, questions were raised about the potential of healing and antioxidant actions. Aiming to make a bibliographic survey of secondary sources of clinical and empirical scientific studies, making an evaluation of different authors on the healing and antioxidant activity of Maytenus ilicifolia. This present integrative literature review research used these databases: Google Scholar, PubMed, Scientific Electronic Librany online (SciELO). Having as an inclusive criterion: responding to the established journal, the search from the DeCS, needing to present the central theme of the research, with a full text available for free, and that present practical clinical activities. After the bibliographic survey, we observed as results that research related to healing action showed some divergences from the final result, in different applications of M. ilicofolia. As for the antioxidant activity, they showed promising results from Maytenus ilicifolia. It was concluded that Maytenus ilicofolia in its extract form showed efficiency under healing action both in the skin and in the gastric tissue (in ulcers), however, in the form of tincture Maytenus ilicofolia had low healing capacity, requiring further studies to elucidate this activity in different preparations. As for the antioxidant action, M. ilicifolia showed characteristics of high antiradical power, eliminating free radicals.